An hp-adaptive finite element method for electromagnetics. Part 3: A three-dimensional infinite element for Maxwell's equations - Cecot, W.; Rachowicz, W.; Demkowicz, L. (International journal for numerical methods in engineering, 2003)
This paper is a continuation of Reference [26] (Cecot, Demkowicz and Rachowicz, Computer Methods in Applied Mechanics and Engineering 2000; 188: 625–643) and describes an implementation of the infinite element for three‐dimensional, time harmonic Maxwell's equations, proposed in Reference [15] (Demkowicz and Pal, Computer Methods in Applied Mechanics and Engineering 1998; 164: 77–94). The element is compatible with the hp finite element discretizations for Maxwell's equations in bounded domains reported in References [16–18] (Computer Methods in Applied Mechanics and Engineering 1998; 152: 103–124, 1999; 169: 331–344, 2000; 187: 307–337). Copyright © 2003 John Wiley & Sons, Ltd.